ШТУЧНИЙ ІНТЕЛЕКТ У РЕСТОРАНАХ ЛЬВОВА: ВПЛИВ НА ОБСЛУГОВУВАННЯ ТА ДОСВІД КЛІЄНТІВ - Fil, Mariya; Bezruchko, Lubomyr; Bilanyuk, Olha; Zhuk, Yuriy (Zhytomyr Ivan Franko State University, 2024)
The introduction of artificial intelligence (AI) into the restaurant business in Lviv faces several significant challenges that require a comprehensive approach to solving them. One of the main challenges is the technical integration of AI into existing restaurant processes. Restaurants must adapt their operating systems to the latest technologies, which require updating software and creating an infrastructure for data processing. The main technological innovations implemented in Lviv restaurants can be divided into several categories: 1. Self-service systems. An example is: McDonald's (selected establishments) - interactive terminals for self-ordering and payment, which significantly speed up the service process and allow you to avoid queues during peak hours. 2. Mobile applications for ordering. Lviv Croissants - a chain of establishments that allows you to order products through the application and pick them up without waiting. Sushi delivery is also known as an application, for example, Osama sushi. In addition to the application, there may also be a website of the establishment, such as Pizza Celentano, Smaki maki, La Piets. 3. Smart queue management systems. Family restaurant "Crazy Town" (Victoria Gardens Shopping Center) - uses a table reservation and queue management system via a mobile application. Table reservations, but via a chat bot, can also be made at the "Hot Bowl" establishment. 4. Automation of food preparation. Salalat - a healthy food establishment where the salad preparation process is automated for faster customer service, including in the take-away format. 6. Order personalization technologies. Premium restaurants in Lviv, such as Park. However, the study also found that the integration of AI requires competent staff training and proper adaptation of technologies to the specifics of the market and consumers. The human factor remains critically important in ensuring a positive customer experience, so the harmonious combination of AI with traditional service methods is key.